C. albicans Detection with Electrochemical Sensors by Using Molecular Imprinted Polymer Technique - Naphatsawan Vongmanee; Jindapa Nampeng; Chuchart Pintavirooj; Sarinporn Visitsattapongse (Polymers, 2026)
, demonstrating that the imprinted cavities effectively distinguish fungal cells from bacterial contaminants. These findings highlight the promise of MIP-based electrochemical biosensors as a simple, low-cost, and portable alternative for early fungal diagnostics.
Keywords: Electrochemical sensors and biosensors; Analytical chemistry methods development; Biosensors and Analytical Detection